Analysis of the implementation of the Si APIK Android-Based Accounting Information System as an Effort to Improve KUBE MSME Income (Joint Bussiness Group) Mega Buana During The Covid – 19 Pandemic - Despita Meisak; Ayu Feranika; Laura Prasasti (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
Apik, an android-based accounting information system, will meet the needs of financial operational activities at MSME Kube Mega Buana in an effort to increase income during the COVID-19 pandemic. This descriptive-qualitative research method is used in applied research. This study's data analysis technique is to collect theories related to the problem, systematically arrange data based on the results of observations or observations made in the field, and describe problems based on theoretical solutions. theory obtained, then the last step is to provide conclusions. Based on the results of the application of the Apik system on MSMES Kube Mega Buana during the trial period, MSMES can carry out simple financial reporting that is in accordance with current accounting standards as a support for increasing income for MSMES. And all evidence of financial transactions is properly archived in the database contained in the application, and transaction history is properly archived every period.